Childhood exposure to intimate partner violence and teen dating violence - Cheung, Shannon P. (Journal of family violence, 2023)
Childhood exposure to intimate partner violence (IPV) has increasingly been studied as a distinct form of child maltreatment with negative outcomes that can last well beyond childhood. The purpose of this study is to examine teen dating violence (TDV) involvement among adolescents who were exposed to IPV in early childhood while controlling for other known risk factors of TDV. We analyze longitudinal data from the Fragile Families and Child Wellbeing Study to investigate the relation between early childhood IPV exposure (Years 1 and 3) and involvement in TDV (Year 15), controlling for parenting behaviors (Year 5), early onset delinquency (Year 9), and other sociodemographic characteristics (baseline). IPV exposure significantly increased TDV involvement, particularly for physical abuse and economic abuse (effect sizes of 0.34 and 0.15, respectively). Based on these findings, providers should implement frequent, comprehensive prenatal and perinatal IPV screenings, referring patients to community services as needed. Also, school-based interventions that promote healthy relationship skills may be targeted to adolescents with early IPV exposure.